Advanced Materials and Nanotechnology for Sustainable Energy and Environmental Applications - Malara, Angela; Frontera, Patrizia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Materials play a very important role in the technological development of a society. As a consequence, the continuous demand for more advanced and sophisticated applications is closely linked to the availability of innovative materials. Although aspects related to the study, the synthesis and the applications of materials are of interdisciplinary interest, in the last few years, great attention has been paid to the development of advanced materials for environmental preservation and sustainable energy technologies, such as gaseous pollutant monitoring, waste water treatment, catalysis, carbon dioxide valorization, green fuel production, energy saving, water adsorption and clean technologies. This Special Issue aims at covering the current design, synthesis and characterization of innovative advanced materials, as well as novel nanotechnologies able to offer promising solutions to the these pressing themes.